THE POSSIBILITY OF THE DETERMINATION OF OIL SATURATION BY THE HELP OF THE FIT COMPLEX OF STATIONARY NEUTRON METHODS - KULYK, V.; BONDARENKO, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the basis of the performed theoretical, experimental and bore hole investigations a basic possibility to determine oil saturation of reservoir with the help of the fit complex of neutron-neutron logging for measuring of the count rate of slow, epithermal and thermal neutrons is presented.